A new discovery: Total Bupleurum saponin extracts can inhibit the proliferation and induce apoptosis of colon cancer cells by regulating the PI3K/Akt/mTOR pathway. (30th January 2022) - Zhang, Xiaojing; Liu, Zhenzhen; Chen, Shuaipeng; Li, Hang; Dong, Lin; Fu, Xueyan
Abstract: Ethnopharmacological relevance: Bupleurum chinense DC has a history of using herb in China for more than 2000 years, which can be traced back to the Classic of Shennong Materia Medica in the Han Dynasty. Although Saikosaponin, the main active ingredient of Bupleurum, has the effects of anti-tumor, yet we still do not know the mechanism by total Bupleurum saponin extracts (TBSE) produces this effect on colon cancer. Aim of the study: It is predicted by network pharmacology that TBSE may play an anti-colon cancer role by regulating the PI3K-Akt-mTOR pathway. The purpose of this study is to investigate whether TBSE inhibits proliferation and promote apoptosis of colon cancer cells by regulating PI3K/Akt/mTOR pathway. Materials and methods: The effect of saikosaponins on the proliferation of SW480 and SW620 cells was detected by CCK-8, apoptosis was determined by flow cytometry, morphological changes of cells were observed by microscope, nuclear morphological changes were observed after immunofluorescence staining, the expression of apoptosis-related proteins Bax, Bcl2, Caspase3, Caspase9, Cleaved Caspase3 and Cleaved Caspase9 were detected by Western Blot, and the expression of apoptosis-related genes Bax, Bcl2, Caspase3 and Caspase9 were detected by RT-PCR. According to the theory of network pharmacology, the potential targets of saikosaponins and colon cancer were predicted by database Pharmmapper and Genecards database respectively. The intersection of saikosaponins and colon cancer was enriched and analyzed on the Metascape platform. Then, the expression of PI3K/Akt/mTOR pathway related protein PI3K, Akt, Mtor, p-PI3K, p-Akt, p-mTOR were detected by Western Blot, and the corresponding amount of RNA expressions in the pathway was confirmed by RT-PCR. Results: The results of CCK-8 demonstrated that the survival rate of SW480 and SW620 cells decreased significantly when the concentration of TBSE was in the range of 25–200 μg/ml. The morphological observation showed that the cells lost normal cell morphology, cytoplasmic condensation, and partial loss of adhesion after treatment with TBSE. Flow cytometry indicated that the apoptosis rates of SW480 cells and SW620 cells treated with TBSE (50 μg/ml) were 48.47% ± 1.20% and 36.13% ± 1.76%, respectively. Western Blot firstly confirmed that TBSE significantly up-regulated the expression of pro-apoptotic proteins Bax, Caspase3, Caspase9, Cleaved Caspase3 and Cleaved Caspase9, and down-regulated the expression of anti-apoptotic protein Bcl2. And RT-PCR results implied that TBSE significantly up-regulated the gene expression of apoptotic factors Bax, Caspase3 and Caspase9, and significantly decreased the gene expression of Bcl2. It was predicted that the PI3K/Akt/mTOR pathway may be the main regulatory object of the antitumor effect of TBSE by network pharmacology. Subsequent WB experiment also revealed that TBSE could significantly down-regulate (P < 0.01) the expressions of PI3K, Akt, mTOR and phosphorylated proteins P-PI3K, P-Akt, P-MTOR. Meanwhile, RT-PCR results also indicated that TBSE could significantly down-regulate (P < 0.01) the gene expression levels of PI3K, Akt and mTOR. Conclusions: TBSE activated Bax/Bcl2 and caspase-9/caspase-3 cascade to induced apoptosis of human colon cancer SW480 and SW60 cells in a dose-dependent manner, which was obviously related to the inhibition of PI3K/Akt/mTOR signaling pathway. Graphical abstract: Image 1